Manajemen Objek Wisata Pantai Pasir Putih Desa Lenju Kecamatan Sojol Utara Kabupaten Donggala - Syuhrahmi; Natsir, Nawawi; Mukarramah (JPS: Journal of Publicness Studies, 2026)
Tourism plays a strategic role in driving national economic growth, making planning and management of tourist attractions crucial. The main problem in this study is the suboptimal management of the Pasir Putih Beach tourist attraction in Lenju Village, characterized by a lack of attention to cleanliness, inadequate facilities, damaged rides, low visitor numbers, and poorly supervised tourist activities. This study aims to determine and understand the management process of the tourist attraction. The method used is a qualitative approach with a descriptive-qualitative type through observation, interviews, and documentation techniques. The results of the study indicate that the management of the Pasir Putih Beach tourist attraction is not running optimally. In the planning aspect, the manager has a development plan, but its implementation is still hampered by land status issues and budget constraints, so it has not been realized optimally. In the organizational aspect, there has been a division of tasks and involvement of various parties in tourism management, so this aspect can be said to have run quite well. In the implementation aspect, management and service activities have not been carried out consistently, which has an impact on the condition of facilities and decreased visitor comfort. Meanwhile, in terms of oversight, monitoring activities have not been optimal due to lack of routine implementation and limited resources, as evidenced by persistent issues with cleanliness, facilities, and activities in tourist areas. Therefore, management needs to improve the implementation of planned programs, strengthen coordination and clarity of tasks between parties, implement management activities routinely and consistently, and enhance ongoing oversight to ensure more effective management of tourist attractions and improve service quality and the number of tourist visits.